The visit of an all-party group of Members of Parliament to Spain : report - Crawford Green, W. P. ; Grenfell, D. R. (David Rhys), 1881-1968 ; James, A. W. ; Macnamara, J. R. J. ; Roberts, Wilfred; Cocks, F. Seymour (Frederick Seymour), b. 1882
1936-12 015b_0033_013 292/946/15b/33(xiii)